2017
DOI: 10.1111/ap.12182
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personality and Workplace Belongingness on Mental Health Workers' Professional Quality of Life

Abstract: Objectives Mental health workers are constantly exposed to their clients' stories of distress and trauma. While listening to these stories can be emotionally draining, professionals in this field still derive pleasure from their work. This study examined the role of personality and workplace belongingness in predicting compassion satisfaction, secondary traumatic stress, and burnout in mental health workers. Methods Mental health staff (N = 156) working in a counselling service completed a questionnaire that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 35 publications
3
48
1
2
Order By: Relevance
“…Although past research has shown that trait‐negative affect relates to secondary traumatic stress in hospital nurses (Craigie et al., ; Măirean, ; Somoray et al., ), the present study is the first to report the relationship between FFM personality traits and secondary traumatic stress in neonatal nurses. Neuroticism had a moderately strong correlation with secondary traumatic stress and neuroticism controlled for work stress made a unique contribution to the variance in secondary traumatic stress.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although past research has shown that trait‐negative affect relates to secondary traumatic stress in hospital nurses (Craigie et al., ; Măirean, ; Somoray et al., ), the present study is the first to report the relationship between FFM personality traits and secondary traumatic stress in neonatal nurses. Neuroticism had a moderately strong correlation with secondary traumatic stress and neuroticism controlled for work stress made a unique contribution to the variance in secondary traumatic stress.…”
Section: Discussionmentioning
confidence: 59%
“…A meta‐analysis by Judge, Heller, and Mount () has shown that FFM neuroticism, agreeableness, extraversion and conscientiousness relate to work satisfaction, and these relationships are stronger and more consistent for neuroticism and extraversion. Although there has not been a study of FFM personality traits and compassion satisfaction in neonatal nurses, agreeableness, extraversion and conscientiousness have been shown to relate to work satisfaction in clinical nurse specialists (Chen, Chen, Tsai, & Lo, ) and compassion satisfaction in mental health professionals (Somoray, Shakespeare‐Finch, & Armstrong, ). Accordingly, one might reasonably expect FFM neuroticism, agreeableness, extraversion and conscientiousness to relate to compassion satisfaction in neonatal nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Germany, Austria and Switzerland [ 82 ]. Samples comprised professionals from diverse occupational groups such as counsellors [ 83 ], mental health social workers [ 76 , 78 , 79 , 80 ], mental health social work doctoral students [ 81 ], mental health nurses [ 84 , 85 , 86 , 87 , 88 ] employee assistance professionals [ 77 ], correctional officers [ 85 ], psychotherapists [ 89 ] and frontline mental health professionals [ 90 ]. The 15 included studies represented a combined sample size of 3356 participants ( M = 239.7, SD = 143), with individual study sample sizes ranging from 36 [ 85 ] to 532 [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 76 , 78 ] used the same dataset, and thus, their data were included only once. Of the nine studies that reported the mean age of participants [ 77 , 79 , 80 , 83 , 84 , 85 , 87 , 89 , 90 ], the combined average age was 47.1 years ( SD = 7.5 years) and ranged from 36.9 years to 59.9 years. In terms of sex distribution, the total number of female participants across all included studies was 1586 (47.3%).…”
Section: Resultsmentioning
confidence: 99%
“…laboral(Faleiros, 2008), ya que cuando los colaboradores se encuentran expuestos al estrés psicológico de las personas de su entorno laboral presentan una mayor carga emocional, que puede deteriorar su calidad de vida profesional y su capacidad para brindar un mejor servicio a la sociedad(Somoray, Shakespeare-Finch & Armstrong, 2017).En este sentido,Villarín, Méndez, Zuzúarregui, Sánchez y Conejo (2015) para conocer la calidad de vida profesional de los médicos de atención primaria del área sanitaria de Toledo, elaboraron un estudio en el cual encontraron que la percepción de apoyo directivo reflejó un valor mínimo y la carga de trabajo un valor intermedio, lo cual se asocia con un deterioro de la calidad de vida profesional total. No obstante, la motivación intrínseca fue alta.…”
unclassified